Research on the Optimal Resource Allocation Algorithm of Power Communication Network - Yang, Hongzhen; Zheng, Xinghang; Shao, Gan; Cai, Qing; Zhou, Xuxiang (IEEE Information Technology, Networking, Electronic and Automation Control Conference (Online), 2021)
The power optical communication network is a dedicated communication network serving the power system, and its survivability is essential to the safe and stable operation of the power system. In this paper, the reliability of the shared path protection algorithm is analyzed and a new parameter-service failure probability is defined, which represents the probability of service failure during transmission; Finally, based on the traditional shared path algorithm, a maximum sharing mechanism is proposed. It can optimize the allocation of spare resources between different services.Simulation calculations and comparative analysis of the CERNET network topology for specific services are carried out. This is of great significance for ensuring the safe and reliable operation of the grid system and reducing the occurrence of large-scale grid accidents.